Convergencia y actividades de aprendizaje en los talleres universitarios de periodismo. Un estudio sobre el Taller Integrado de Periodismo de la Universitat Pompeu Fabra (2018)
This article examines journalism workshops as learning scenarios in the context of media convergence. It’s a case study, the Integrated Journalism Workshop (TIP) of the Pompeu Fabra University, which includes the television, radio, press and Internet sections. As an introduction, the study presents the characteristics and constructivist paradigms that defining these spaces, and the convergent particularity of the TIP. For this research, a qualitative methodology was applied that combined the techniques of observation in newsrooms, radio, television and internet section and semi-structured interviews with four teachers -one for each section- and the TIP coordinator. The analysis of the information gathered allowed us to conclude that this space is configured as a scenario of authentic learning activities, by placing the student in real situations of the profession, through collaborative work and joint critical reflection.